Is the brain of complex regional pain syndrome patients truly different?. (10th May 2016) - van Velzen, G.A.J.; Rombouts, S.A.R.B.; van Buchem, M.A.; Marinus, J.; van Hilten, J.J.
Abstract: Background: In recent years, changes in brain structure and function have been studied extensively in patients with complex regional pain syndrome (CRPS) following clinical observations of altered central processing of sensory stimuli and motor control. However, concerning MRI data, the evidence is complex to interpret due to heterogeneity in statistical methods and results. Method: The aim of this study was to determine if CRPS patients exhibit specific, clinically relevant changes in brain structure and function in rest. We do this by presenting MRI data on brain structure and function in 19 chronic, female CRPS patients and age‐ and sex‐matched healthy controls (HCs). In addition, we analyse and report the data in multiple ways to make comparison with previous studies possible and to demonstrate the effect of different statistical methods, in particular, concerning the correction for multiple testing. Results: Using family‐wise error (FWE) correction for multiple testing, in our group of CRPS patients, we find no specific difference in brain structure or function in rest in comparison to HCs. In addition, we argue that previously found MRI results in the literature are inconsistent in terms of localization, quantity and directionality of the reported changes in brain structure and function. Conclusion: Previously published MRI‐based evidence for altered brain structure and function in rest in CRPS patients is not consistent and our data suggests that no such phenomenon exists. What does this study add?: This article does not replicate the previous found results. The reported evidence in MRI literature of aberrant neuroplasticity in CRPS patients is inconsistent in terms of localization, quantity and directionality of changes in brain structure and function.